Analisis dan Implementasi Proses Quality Assurance pada Pengembangan Aplikasi Point of Sale di PT. Olsera Indonesia Pratama - Ferdynand Kee; Nimatul Ma'muriyah; Andik Yulianto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2025)
This practical work activity focuses on the analysis and implementation of the Quality Assurance (QA) process in the development of a Point of Sale (POS) application at PT. Olsera Indonesia Pratama. The main objective of this activity is to apply a systematic testing process to ensure software quality and stability before its release to end-users. The implementation method adopts the Agile workflow applied within the company, utilizing a hybrid testing approach that combines manual testing for complex features and basic automation testing for efficiency. The testing process used the Black Box Testing method on various features across multiple platforms, including mobile and web applications. The results of the implementation show that a structured QA process successfully identified various functional and non-functional issues, validated bug fixes effectively, and ensured that key features like